Analytical model tracing deformations in multistorey large timber panel building - Malesza, Jaroslaw; Miedzialowski, Czeslaw; Ustinovichius, Leonas (Journal of Civil Engineering and Management, 2019)
This paper deals with the deformation characteristics of wood-framed residential, small commercial and hotel buildings with sheathing. Recent building structures are based on large panel or modular technology, where elements in the form of diaphragms or modules are constructed in an industrial plant and then transported to the site for assembly. The document presents diagrams of building assembly and technologies for realization. The significant influence of excessive vertical deformations in multistorey wood-framed buildings on their performance and serviceability is underlined. These deformations are caused by different factors which are identified and analytically described. The paper outlines the analytically complex model for the evaluation and control of deformations in the design, construction and exploitation of multistorey wood-framed buildings. An example of the application of the proposed analytical model at the design stage concludes the paper.